Performance enhancement of shunt active power filter using soft computing techniques - Annu Govind; Vijay Kumar Tayal; Prakash Kumar (Institute of Advanced Engineering and Science, 2021)
Nowadays, active power filter (APF) is the most popular device for harmonic compensation. This paper presents the soft computing techniques for compensation of currents harmonics using a shunt active power filter (SAPF). The method includes a 3-phase supply system with a current-controlled voltage source converter (CC-VSC) having an input coupling inductor and output tank capacitor for a self-supported DC bus. The performance of the active power filter can be enhanced by using soft computing techniques such as artificial neural network (ANN) controller and gravitational search algorithm (GSA) for generating control signals of the SAPF. The current reference is calculated to compensate source current THD with synchronous reference frame (SRF) technique with proportional integrator (PI) controller. From the result, it is evident that both the soft computing techniques reduce the computational time & fast convergence which improves the filter performance during the transient period and makes it self-tuned. The proposed structure is simulated using MATLAB/Simulink and subsequently experimentally verified. The presentation of the system is originated to be suitable for numerous features of power quality enhancement structure.